Degradation in fundamental characteristic features of Bi-2212 superconducting ceramic material with Sr/Ti partial substitution - Ülgen, Asaf Tolga; Yıldırım, Gürcan (JOURNAL OF MATERIALS SCIENCE-MATERIALS IN ELECTRONICS, 2019)
The present work investigates the vital differentiations in some basic characteristic properties including the crystallinity quality, flux pinning mechanism, superconducting, dc electrical features, grain boundary coupling problems and strength of connection between the superconducting grains in the poly-crystallized Bi2.1Sr2.0-xTixCa1.1Cu2.0Oy cuprate ceramic materials with the partial aliovalent substitution of Sr2+ impurities for the Ti4+ foreign additives in the crystal system. All the materials are prepared by the standard solid-state reaction method, and the characterization of samples produced is thoroughly performed by the typical experimental measurements such as dc electrical resistivity over the temperature, critical current density and powder X-ray diffraction investigations. It is obvious that all characteristic properties tend to diminish constantly with the augmentation of the aliovalent Sr/Ti partial replacement level, and in case of x=0.10 they reach the global minimum values. To illustrate, the low Bi-2212 superconducting phase diverges from the stabilization because of new induced permanent crystal structure (crystallinity) problems such as the voids, porosity, defects, texturing, cracks, grain boundary coupling problems, grain alignment distributions, stress raisers, omnipresent flaws and crack initiation sites in the crystal system. Besides, the presence of Ti impurities leads to the formation of new impurity phases related to very low superconducting and characteristic TiO2 phase, being favored by either the decrement of c lattice cell parameter or increment of a-axis length. The similar findings are observed in the temperature dependent electrical resistivity measurements. Namely, the electrical resistivities at the normal state are found to increase dramatically from about 74.75-180.47 mcm whereas the offset and onset critical temperature values are recorded to diminish from 82.11K (for the pure sample) to 50.52K (for the sample prepared with x=0.10 substitution level) and 84.03-75.14K, respectively, with the enhancement in the substitution level. Likewise, the Sr/Ti partial replacement affects negatively not only the thermal fluxon motions of correlated two-dimensional pancake vortices but also the ability and strength of vortex lattice period, elasticity, effective and active energy barriers for the flux pinning centers in the Bi-2212 superconducting crystal lattice. In this respect, the Sr/Ti partial substitution mechanism is ploughed to improve the fundamental characteristic features.
Keywords: CRITICAL-CURRENT-DENSITY; INSULATOR TRANSITION; TRANSPORT-PROPERTIES; SYSTEM; METAL; GD